Revision of Bryobiella Tuttle & Baker (Acari, Tetranychidae), with ontogenetic development and redescription of B. desertorum - Yi, Tian-Ci; Ochoa, Ronald (Zootaxa, 2018)
The genus Bryobiella Tuttle & Baker is redescribed with a revised diagnosis. The type species B. desertorum is redescribed based on larvae, protonymphs, deutonymphs and adults including the paratype male. Morphological differences from different host plants are noted, as are some intraspecific variations not associated with host plants. The ontogenetic development of leg setae shows some departures from the typical patterns known in the Tetranychoidea, such as males adding solenidia to the femur and genu of leg I and femur, genu and tibia of leg II. A key to species of Bryobiella based on females is given.